Understanding the preterm human heart: what do we know so far? - Schuermans, A; Lewandowski, AJ (Wiley, 2022)
Globally, preterm birth affects more than one in every 10 live births. Although the short-term cardiopulmonary complications of prematurity are well known, long-term health effects are only now becoming apparent. Indeed, preterm birth has been associated with elevated cardiovascular morbidity and mortality in adulthood. Experimental animal models and observational human studies point toward changes in heart morphology and function from birth to adulthood in people born preterm that may contribute to known long-term risks. Moreover, recent data support the notion of a heterogeneous cardiac phenotype of prematurity, which is likely driven by various maternal, early, and late life factors. This review aims to describe the early fetal-to-neonatal transition in preterm birth, the different structural and functional changes of the preterm human heart across developmental stages, as well as potential factors contributing to the cardiac phenotype of prematurity.